Renal Cell Carcinoma in the Geriatric Population: Toward a Frailty-Adapted Therapeutic Paradigm - Cemile Ozsurekci; Ufuk Yazar; Yusuf Acikgoz (Journal of Clinical Medicine, 2026)
Background: Renal Cell Carcinoma (RCC) primarily affects older adults, with incidence increasing with age. Older adults remain underrepresented in clinical trials, and treatment decisions are often extrapolated from younger populations. Age-related factors such as comorbidities, frailty, polypharmacy, and immunosenescence complicate management in the geriatric population. Methods: A narrative review of the literature was conducted, focusing on localized and metastatic RCC in older adults. The review comprehensively examined the following topics: surgical interventions, active surveillance strategies, systemic therapies (including immune checkpoint inhibitors, vascular endothelial growth factor tyrosine kinase inhibitors, and hypoxia-inducible factor-2α (HIF-2α) inhibitors), toxicity profiles, and real-world outcomes. Results: Managing RCC in older adults requires balancing efficacy with tolerability. For localized disease, surveillance and minimally invasive approaches are suitable given mortality risks. In metastatic RCC, immune checkpoint inhibitor combinations and targeted therapies have improved outcomes, though toxicity may increase in frail patients. Given the favorable safety profile of HIF-2α inhibitors, these agents may play a more substantial clinical role and offer improved therapeutic utility in this patient population. Real-world data show disparities between trial populations and practice, highlighting the need for individualized treatment. Conclusions: RCC management in geriatric patients requires a shift from age-based to frailty-informed decisions. Integrating geriatric assessment enables better patient selection and treatment tailoring. Future research should focus on geriatric-adapted trials, biomarker strategies, and de-escalation approaches to improve outcomes while reducing toxicity in this population.